2008
DOI: 10.1111/j.1553-2712.2008.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Atropine Is Unnecessary during Ketamine Sedation in Children

Abstract: Background: The prophylactic coadministration of atropine or other anticholinergics during dissociative sedation has historically been considered mandatory to mitigate ketamine-associated hypersalivation. Emergency physicians (EPs) are known to omit this adjunct, so a prospective study to describe the safety profile of this practice was initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 17 publications
2
17
0
1
Order By: Relevance
“…1,2 Our study showed no efficacy for either anticholinergic in reducing airway complications and support the conclusion of Brown et al 2 that coadministered anticholinergics are not routinely necessary during ketamine sedation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…1,2 Our study showed no efficacy for either anticholinergic in reducing airway complications and support the conclusion of Brown et al 2 that coadministered anticholinergics are not routinely necessary during ketamine sedation.…”
Section: Discussionsupporting
confidence: 83%
“…1,2 Their efficacy in this role is controversial, with study results both pro 3 and con. 2,4,5 It is possible that the conflicting evidence on this issue results from differences between the two anticholinergics typically used-atropine and glycopyrrolate. Unlike atropine, the synthetic glycopyrrolate does not cross the blood-brain barrier and thus exhibits less influence on the central nervous system.…”
mentioning
confidence: 99%
“…32 A large case series of patients showed the safety profile of ketamine when coadministered anticholinergics were omitted and excessive salivation was uncommon. 33 With ketamine use there has been concern for laryngospasm, which is uncommon. Laryngospasm is typically easily corrected with bag-valve mask ventilation.…”
Section: Dissociative Agents Ketaminementioning
confidence: 99%
“…Il n'y a pas de bénéfice à associer à la kétamine ni l'atropine [2] ni une benzodiazépine. Une étude pharmacodynamique a précisé le profil de la kétamine chez 43 enfants [14] : la concentration plasmatique de 1,5 mg/l est atteinte, en trois à quatre minutes, chez 95 % des enfants ayant reçu par voie i.v.…”
Section: Autres éTudes Cliniquesunclassified